VD_FINDINFO HC / 2011 / 297 vom 31. Mai 2011 - VD Tribunal cantonal (2011)
FORMALISME EXCESSIF, BIEN-FONDS, INTERDICTION, RECTIFICATION DE LA DÉCISION | 420 CPC, 334 al. 3 CPC (CH), 404 al. 1 CPC (CH)